Closing the Critical Period Is Required for the Maturation of Binocular Integration in Mouse Primary Visual Cortex - Chan, Jiangping; Hao, Xiangwen; Liu, Qiong; Cang, Jianhua; Gu, Yu (Frontiers in Cellular Neuroscience, 2021)
Binocular matching of orientation preference between the two eyes is a common form of binocular integration that is regarded as the basis for stereopsis. How critical period plasticity enables binocular matching under the guidance of normal visual experience has not been fully demonstrated. To investigate how critical period closure affects the binocular matching, a critical period prolonged mouse model was constructed through administration of bumetanide, an NKCC1 transporter antagonist. Using acute in vivo extracellular recording and molecular assay, we revealed that binocular matching was transiently disrupted due to heightened plasticity after the normal critical period, together with an increase in the density of spines and synapses, and upregulation of GluA1 expression. Diazepam/CPP could reclose the extended critical period, and rescue the deficits in binocular matching. Furthermore, the extended critical period alone with normal visual experience is sufficient for the completion of binocular matching in amblyopic mice. Similarly, prolonging the critical period into adulthood by knocking out Nogo-66 receptor can prevent the normal maturation of binocular matching and depth perception. These results suggest that maintaining an optimal plasticity level during adolescence is most beneficial for the systemic maturation. Extending the critical period provides new clues for the maturation of binocular vision and may have critical implications for the treatment of amblyopia.